Ondansetron: recommended antiemetics for patients with acute pancreatitis? a population-based study - Wu, Ge; Ma, Yifei; Wei, Wanzhen; Zeng, Jiahui; Han, Yimin; Song, Yiqun; Wang, Zheng; Qian, Weikun (Frontiers in Pharmacology, 2023)
Objective: Ondansetron administration is a common antemetic of acute pancreatitis therapy in the intensive care unit (ICU), but its actual association with patients' outcomes has not been confirmed. The study is aimed to determine whether the multiple outcomes of ICU patients with acute pancreatitis could benefit from ondansetron. Methods: 1,030 acute pancreatitis patients diagnosed in 2008-2019 were extracted from the Medical Information Mart for Intensive Care (MIMIC)-IV database as our study cohort. The primary outcome we considered is the 90-day prognosis, and secondary outcomes included in-hospital survival and overall prognosis. Results: In MIMIC-IV, 663 acute pancreatitis patients received ondansetron administration (OND group) during their hospitalization, while 367 patients did not (non-OND group). Patients in the OND group presented better in-hospital, 90-day, and overall survival curves than the non-OND group (log-rank test: in-hospital: P < 0.001, 90-day: P = 0.002, overall: P = 0.009). After including covariates, ondansetron was associated with better survival in patients with multiple outcomes (in-hospital: HR = 0.50, 90-day: HR = 0.63, overall: HR = 0.66), and the optimal dose inflection points were 7.8mg, 4.9mg, and 4.6mg, respectively. The survival benefit of ondansetron was unique and stable in the multivariate analyses after consideration of metoclopramide, diphenhydramine, and prochlorperazine, which may also be used as antiemetics. Conclusion: In ICU acute pancreatitis patients, ondansetron administration was associated with better 90-day outcomes, while results were similar in terms of in-hospital and overall outcomes, and the recommended minimum total dose might be suggested to be 4-8mg.